Alkaline salts to counteract bone resorption and protein wasting induced by high salt intake: results of a randomized controlled trial - Bühlmeier, Judith; Maser-Gluth, Christiane (The journal of clinical endocrinology & metabolism, 2012)
High sodium chloride (NaCl) intake can induce low-grade metabolic acidosis (LGMA) and may thus influence bone and protein metabolism.We hypothesized that oral p